DIFFERENCES IN CULTURAL COMPETENCE FOR ARAB IMMIGRANT WOMEN BASED ON FAMILY, WORKING, AND MOTHERHOOD STATUS - Alsaraj, Nour (E-Journal VFU, 2025)
This study explores the role of cultural competence in the sociocultural adaptation of Arab immigrant women and examines how their marital status, employment status, and motherhood impact their adaptation. Cultural competence is essential for navigating societal expectations and overcoming barriers to inclusion. The integration experiences of Arab women are influenced by their employment, family status, and degree of social engagement. The current study employed a quantitative research approach, surveying 300 Arab immigrant women from Türkiye, Bulgaria, and England. Validated instruments, such as the Sociocultural Adaptation Scale (SCAS), evaluated adaptation outcomes. The findings indicated that working women exhibited higher levels of cultural competence and social integration than unemployed women and stay-at-home mothers, as they benefited from greater exposure to multicultural environments and more opportunities for professional interactions. In contrast, unemployed women and stay-at-home mothers reported feeling more isolated, primarily depending on their ethnic networks for social interactions, which created both opportunities and barriers in their integration process. Additionally, the marital status of Arab women can significantly affect their integration, as married women may face additional barriers resulting from cultural expectations that limit their freedom of movement and participation in social and professional roles. Conversely, single women might experience greater independence but encounter societal pressures to seek autonomy. Another layer of complexity surrounding integration and adaptation for Arab immigrant women involves motherhood. Mothers must navigate their cultural identity while helping their children adapt to European societal expectations. This study emphasizes the importance of implementing targeted actions, such as promoting workplace diversity initiatives, encouraging community participation, and enhancing cultural competence initiatives, to bridge the adaptation gap for Arab immigrant women. Policymakers can create a framework for inclusion and well-being when designing an integration strategy by considering the interplay of marital status, employment, and motherhood. If Europe aims to support Arab immigrant women in overcoming cultural challenges, enhancing access to economic opportunities, and fostering a culture-specific understanding of their integration experiences is vital.
Keywords: Cultural Competence; Arab Immigrant Women; Marital Status; Work Status; Motherhood Status